Nuclear-Localized Fluorescent Proteins Enable Visualization of Nuclear Behavior in the Basidiomycete Schizophyllum commune Early Mating Interactions - Raudaskoski Marjatta; Butler-Hallissey Ciarán (MDPI, 2025)
Spinning disc confocal microscopical research was conducted on living mating hyphae of the tetrapolar basidiomycete Schizophyllum commune. Haploid strains with either the same or different A and B mating-type genes and expressing differently labelled histone 2B were confronted. In the haploid hyphae histone 2B mCherry and histone 2B EGFP were visualized as red and green nuclei, respectively. In hyphae with the same A but different B genes, the red and green nuclei were observed next to each other. This indicated that nuclear migration between strains, regulated by the B mating type, had taken place. The compatible mating with different A and B genes produced a high number of mixed EFGP/mCherry, yellow nuclei. The mixed nuclei resulted from nearby divisions of nuclei encoding different histones and mating-type genes. During this process, the histones with the different labels were incorporated in the same nuclei, along with the heterodimerized transcription factors encoded by the different A mating-type genes and present around the nuclei. This led to the activation of the A-regulated pathway and indicated that different A genes are important to the cell cycle activation of a compatible mating. Consequently, a yellow nuclear pair stuck together, divided synchronously and proceeded in the migration hyphae towards the colony periphery, where the dikaryotization was promoted by branch formation from the migration hyphae.